2016
DOI: 10.1017/s0144686x16001434
|View full text |Cite
|
Sign up to set email alerts
|

Care-giving to grandchildren and elderly parents: role conflict or family solidarity?

Abstract: Intergenerational help and care among members of the family belong to the most important dimensions of contemporary welfare regimes. Recent research has indicated that a major part of caring responsibilities is placed on the middle-aged generation. The ‘pivot generation’ is expected to provide help to their adult children and grandchildren as well as to their ageing parents. It has been hypothesised that people helping their parents are discouraged from looking after their grandchildren because they experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 57 publications
(71 reference statements)
1
26
0
Order By: Relevance
“…As observed elsewhere (e.g. Grundy and Henretta 2006, Železná 2018), these participants typically considered care for the young to be a natural priority.…”
Section: Resultsmentioning
confidence: 55%
“…As observed elsewhere (e.g. Grundy and Henretta 2006, Železná 2018), these participants typically considered care for the young to be a natural priority.…”
Section: Resultsmentioning
confidence: 55%
“…Recent research evidence demonstrates that it is the generation of grandparents rather than parents who, to a greater extent, belongs to the sandwiched generation involved in various multigenerational care duties (Grundy & Henretta, 2006;Zhang et al, 2018;Železnă, 2018).…”
Section: Work and Family Life In Middle-age And Later Life: The Role mentioning
confidence: 99%
“…Recent research evidence demonstrates that it is the generation of grandparents rather than parents who, to a greater extent, belongs to the sandwiched generation involved in various multigenerational care duties (Grundy & Henretta, 2006; Železnă, 2018; Zhang, Emery, & Dykstra, 2018). The situation where care duties accumulate rather than competing may indicate a strong sense of family solidarity and an overall tendency to care (Železnă, 2018). This, however, does not need to reduce the potential risks of overburden among those who engage in such activities (Železnă, 2018).…”
Section: Work and Family Life In Middle-age And Later Life: The Role mentioning
confidence: 99%
See 1 more Smart Citation
“…As time is a finite resource, engagement in one activity often takes place at the expense of involvement in another. However, the few existing studies addressing provision of help to more than one generation do not give any indication of a zero-sum phenomenon in the family: helping one generation does not seem to reduce the likelihood of helping another (Grundy and Henretta 2006;Fingerman et al 2011;Vlachantoni et al 2019;Železná 2018). Actually, Grundy and Henretta (2006), as well as Vlachantoni et al (2019) and Železná (2018), have concluded that providing help and care to parents increases the probability of helping younger generations, not the contrary.…”
Section: Introductionmentioning
confidence: 99%